THE ANTICLERICAL NEWSPAPER A LANTERNA AND THE ICONOGRAPHIC REPRESENTATION OF THE FERRER MYTH (SAO PAULO, 1909-1916) - Oliveira, Ana Paula Neves de [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2024)
This article focuses on the analysis of iconographic materials published in A Lanterna - Folha anticlerical de combate (S & atilde;o Paulo, 1909-1916), seeking to think about the production, circulation, reception, acclimatization and consequent appropriation of the figure of the Catalan educator Francisco Ferrery Guardia in the newspaper. The iconographic sources were systematized into three thematic series, which were used to deepen the analysis. Anchored fundamentally in Roger Chartier's theories on disputes over representations and Raoul Girardet's theories on political myths, the aim is to demonstrate the hypothesis that the figure of Ferrer was constructed as a political myth in order to expand the newspaper's anticlerical discourse. In addition, attention is drawn to the circulation of some of this material, highlighting, where possible, its origin and outlining possibilities for its transnational diffusion.
Keywords: ALanterna; Francisco Ferrer; Anti-clericalism; Iconography; Brazil's First Republic